Spatial market integration of wheat and rice in Pakistan and South Asia - Sahito, Jam Ghulam Murtaza; Justus Liebig University Giessen (My University, 2015)
Wheat and rice are important staple food crops of South Asian countries including Pakistan. Wheat and rice trade across South Asian countries takes place not only to earn foreign exchange but to ensure food security also. Market integration and transmission of price information ow is required to facilitate the process of trade among South Asian countries. Previous research on the subject has attempted at analyzing market integration in Pakistan´s south and north Punjab regions, mainly relying on cointegration only and not considering advanced dynamic models and transaction costs to analyze the degree of integration. Therefore, this study is a first attempt to analyze the extent of market integration in the whole country using a TVECM model. Monthly wholesale price data of five regional markets of wheat and seven markets of rice from January 1988 to April 2011 were used for this study. Cointegration was also identified in all the price series pairs of wheat and ice using the Johansen´s cointegration test. The Threshold Vector Error Correction Model (TVECM) with a band of non-adjustment was applied to incorporate transaction costs, without relying on observations for these costs, which were not available for the study. Hence, the TVECM was preferred over a simple VECM.For a complete analysis and comparison, VECM results are also presented and discussed. Results of the analysis revealed that wheat and rice markets of Pakistan are quite integrated in the long run as well as in the short run. It was found that linear ECMs or VECMs provide misleading results as compared to TVECMs. Short-run adjustments in the TVECM model provide mixed results depending on regimes as well as markets. Strong adjustments were found in the upper regime, which shows that when price differences are above the second threshold markets tend to adjust significantly.Market integration analysis of South Asia includes monthly wholesale prices of Bangladesh, India and Pakistan only, because of the unavailability of data for other countries in the region. Along with that, wheat export price series of the United States of America (US-HRW) and Thailand and Vietnam rice export prices were used to investigate market integration of South Asian countries with the world markets. Time series for South Asian wheat markets and for US-HRW price series starts from January 2000 and it ends to June 2011. The Johansen´s cointegration test revealed long-run integration for almost all the pairs of wheat and rice markets. The VECM estimates showed that Indian domestic market prices do not adjust significantly with any of the other market under study. Pakistan and Bangladesh wheat markets have shown slow but significant adjustment with the changes in the US-HRW wheat export prices. Wheat market prices of Pakistan have also revealed significant adjustment to the shock appeared in Bangladesh or Indian market prices while adjustment from Bangladesh wheat market has been noticed only in response to the shock in Indian wheat prices. Overall, the coefficient of the adjustment parameter has been very low.Estimation results obtained from the application of the TVECM depicted a different story. Statistically significant adjustment parameters were found in the case of wheat markets of Pakistan and India also. Along with that Pakistani wheat markets have shown significant adjustment to the changes in Bangladesh wheat prices as well as to the international prices. Whereas, Bangladesh markets have shown significant and higher adjustment in response to the changes in Indian wheat prices. No significant adjustment of Bangladesh and Indian wheat markets can been seen in result of the changes in the international wheat market.The TVECM estimations show that the Indian market is less integrated with the international markets, mainly because of their government interventions in the rice sector. For instance, they imposed a ban on the trade of wheat and rice after 2007 for couple of years. A higher degree of integration can be achieved with extended cooperation and by facilitating trade within the region, which will reduce the costs of trade, stabilize the prices in the region and will also be helpful in ensuring food security in the region. These objectives can be achieved by an efficient functioning of markets, by reducing government interventions and by encouraging private traders to participate actively.
Keywords: Market Integration; VECM; TVECM; ddc:330